The Role of the Village Government as Stabilizer in the Management of Village Assets in Sidoarjo Regency: Peran Pemerintah Desa Sebagai Stabilisasi dalam Pengelolaan Aset Desa di Kabupaten Sidoarjo - Widiyaningrum, Ayu; Choiriyah, Ilmi Usrotin (Indonesian Journal of Public Policy Review, 2021)
This study aims to describe and analyze the Role of the Village Government as a Stabilizer in Village Asset Management in Temu Village, Prambon District, Sidoarjo Regency. The research method used is descriptive qualitative method with data collection techniques used through interviews, observation, and documentation. The technique of determining the informants in this study used purposive sampling, there were 3 informants in this study, namely the Head of the Temu Village as the Key Informant and the Secretary of the Temu Village as the informant. The data obtained were processed by qualitative data analysis techniques, namely data collection, data reduction, data presentation, and drawing conclusions. The results showed that the Role of the Village Government as a Stabilizer in Village Asset Management in Temu Village, Prambon District, Sidoarjo Regency in its role as a stabilizer that was successfully carried out by providing guidance and community empowerment through coaching provided by cooperating with the Department of Agriculture in delivering material is an effort of the village government to welfare and develop village communities through the income generated in the management of village assets. In addition to the guidance provided by the government, the Temu Village Government conducts a village treasury land rental auction to minimize monopoly by certain parties and to give the village community the opportunity to take advantage of village assets. And as an approach to building good relations between the Temu Village Government and the village community.